Application of Taguchi Method for Characterization of Corrosion Behavior of TiO2 Coating Prepared by Sol‐Gel Dipping Technique. Issue 5 (28th May 2013) - Naghibi, Sanaz; Jamshidi, Amin; Torabi, Omid; Kahrizsangi, Reza E.
<x xml:space="preserve">Abstract</x> Titanium oxide (TiO2) nanoparticle coatings were deposited on the 316L stainless steel substrates by sol‐gel method. The morphology, structure, and corrosion resistance of the coating were analyzed using SEM, AFM, X‐ray diffraction, and electrochemical techniques. The deposition parameters employed to realize the anticorrosion performance including calcinations temperature, polyethylene glycol (PEG) content, pH value, and number of dipping cycles were investigated. Taguchi statistical experiments were carried out to determine the influence of the deposition variables on anticorrosion properties and optimal conditions. The results indicated that a higher anticorrosion performance of TiO2 films could be achieved using 1 g of PEG in a sol with pH in range of 7–9, six cycles of dipping, and calcination temperature at 400°C. The Tafel polarization measurements indicate that icorr value decreases about 200 times and the Rcorr value increases around 57 times compared with uncoated 316L stainless steel.